Internal and external determinants of the use of supplementary pension plans in manager compensation - Revuelto-Taboada, Lorenzo (2023)
This study scrutinizes the use of supplementary pension plans (SPPs) in the executive compensation strategies of multinational and multi-Latin firms. The proposed analysis focuses on the internal and external factors that may influence the implementation of SPPs and their role in attracting, retaining, and motivating strategically valuable human capital in the form of executive managers. The analysis was based on in-depth interviews with a range of managers, representatives of multilateral institutions, researchers, and heads of pension funds and mandatory pension plans. Relevant complementary data was obtained from a variety or documentary sources. The paper offers valuable findings and implications for the design of compensation strategies of senior managers of multinational and multi-Latin firms. The study also has implications regarding the use of loyalty mechanisms aimed at developingcompetitive advantages to enhance business performance.